The Efficacy of Achillea Millefolium Topical Gel Along with Intralesional Injection of Glucantime in the Treatment of Acute Cutaneous Leishmaniasis - Fariba Jaffary; Mohammad Ali Nilforoushzadeh; Naser Tavakoli; Behzad Zolfaghari; Foroud Shahbazi (مجله دانشکده پزشکی اصفهان, 2012)
Background: Leishmaniasis is still one of the endemic parasitic infections in many countries, such as Iran. During the past decades, many reaserches have studied medical and surgical approaches to treatment of cutaneous leishmaniasis in Iran and the world in order to achieve the best option. However, there is still no single definite and unique approach available for treatment of this disease with optimal safety and efficacy. Some clinical studies have focused on topical use of traditional herbs, such as Achilles millefolium (Yarrow), as an adjutant treatment of cutaneous leishmaniasis along with other approaches, and showed its suitable impact on the healing of lesions. This study was carried out to evaluate the effect of topical Achilles millefolium in conjunction with intralesional glucantime on acute cutaneous leishmanial lesions. Methods: sixty patients with confirmed acute cutaneous leishmaniasis were recruited in this study. Patients were randomly allocated to two groups to receive topical gel of Achilles millefolium 5% twice daily (containing 5% polyphenol) (group A) or placebo (group B) for four weeks along with a weekly injection of intralesional Glucantime. Findings: There was no significant difference between the two groups according to age, gender, and duration of the disease. Moreover, there was no significant difference in complete and relative cure rates between the two groups (P = 0.35). Application site reactions occurred in 12 patients; including redness in 8 cases in group A and 2 cases in group B, severe itching in 1 case in group A, and increasing of wound secretion in another case in group A (P = 0.014). Conclusion: Given the results of the present study, there is no significant difference in cure rates of lesions between yarrow and placebo topical gels as adjuvant drugs with intralesional glucantime in the treatment of acute cutaneous leishmanial lesions.